Increasing evidence of the role of Helicobacter pylori SabA in the pathogenesis of gastroduodenal disease - Yamaoka, Yoshio (2008)
Although infection with Helicobacter pylori always results in chronic active gastritis, only a fraction of those infected develop severe clinical disease. In addition, certain populations with high incidences of H. pylori infection, such as those in East Asian countries, have high incidences of gastric cancer, while other highly infected populations, such as those in Africa and South Asia, do not. This phenomenon might be partially explained by differences in the genotypes of H. pylori; however, currently no definite H. pylori factors can clearly explain it. Recently, the importance of sialic acid binding adhesin (SabA), a novel outer membrane protein in gastroduodenal pathogenesis, has become increasingly apparent. Binding of blood group antigen binding adhesin (BabA) to Lewis b antigen and related fucosylated ABO blood group antigens is probably important in the initial stage of infection. However, when host inflammation increases, expression of sialyl-Lewis×increases, and H. pylori is likely to adhere to the gastric mucosa with SabA. Many of the genes encoding outer membrane proteins undergo phase variation such that not all strains will produce functional proteins, and SabA expression is frequently switched “on” or “off”, suggesting that SabA expression can rapidly respond to changing conditions in the stomach or in different regions of the stomach. SabA production is indeed reported to be associated with severe intestinal metaplasia, gastric atrophy, and the development of gastric cancer in both developed and developing countries, confirming the importance of investigating SabA in developing countries.